664.641.11 ANALYSIS OF THE PROSPECTIVENESS AND SAFETY OF THE USE OF PLANT RAW MATERIALS IN THE ENRICHMENT OF FLOUR AND BREAD PRODUCTS - KHOSHIMOVA, NAZIRA (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This article provides information on measures to prevent micronutrient deficiency, which is one of the most important problems of the population.The creation of products containing a wide range of biologically active nutrients for mass consumption remains an urgent task today. The growing attention to the use of local raw materials in production is causing great interest in obtaining additional nutrients from various plants in our country.